Seeming confines: Electrophysiological evidence of peripersonal space remapping following tool-use in humans. (November 2021) - Ronga, Irene; Galigani, Mattia; Bruno, Valentina; Castellani, Nicolò; Rossi Sebastiano, Alice; Valentini, Elia; Fossataro, Carlotta; Neppi-Modona, Marco; Garbarini, Francesca
Abstract: The peripersonal space (PPS) is a special portion of space immediately surrounding the body, where the integration between tactile stimuli delivered on the body and auditory or visual events emanating from the environment occurs. Interestingly, PPS can widen if a tool is employed to interact with objects in the far space. However, electrophysiological evidence of such tool-use dependent plasticity in the human brain is scarce. Here, in a series of three experiments, participants were asked to respond to tactile stimuli, delivered to their right hand, either in isolation ( unimodal condition ) or combined with auditory stimulation, which could occur near ( bimodal-near ) or far from the stimulated hand ( bimodal-far ). According to multisensory integration spatial rule, when bimodal stimuli are presented at the same location, we expected a response enhancement (response time – RT – facilitation and event-related potential – ERP – super-additivity). In Experiment 1, we verified that RT facilitation was driven by bimodal input spatial congruency, independently from auditory stimulus intensity. In Experiment 2, we showed that our bimodal task was effective in eliciting the magnification of ERPs in bimodal conditions, with significantly larger responses in the near as compared to far condition. In Experiment 3 (main experiment), we explored tool-use driven PPS plasticity. Our audio-tactile task was performed either following tool-use (a 20-min reaching task, performed using a 145 cm-long rake) or after a control cognitive training (a 20-min visual discrimination task) performed in the far space. Following the control training, faster RTs and greater super-additive ERPs were found in bimodal-near as compared to bimodal-far condition (replicating Experiment 2 results). Crucially, this far-near differential response was significantly reduced after tool-use. Altogether our results indicate a selective effect of tool-use remapping in extending the boundaries of PPS. The present finding might be considered as an electrophysiological evidence of tool-use dependent plasticity in the human brain.